The Effect of School Climate on Teaching Satisfaction: The Role of Teacher Engagement - Pal, Raj Kumar; Dey, Antara; Roy, Nil Ratan (Voices of Teachers and Teacher Educators, 2024)
When teachers like working in the environment of a school, they are more likely to be satisfied with their professional lives. The relevance of school climate in sustaining productive learning settings for students and secure, healthy working conditions for faculty has been repeatedly seen in researches. This research looks at how teachers’ levels of engagement may serve as a mediator between their perceptions of the school climate and their levels of job satisfaction. A total of 476 secondary school educators from 49 public institutions took part in this survey. The study has found positive and statistically significant impact of school climate on the view of teachers about their work and job satisfaction with a strong positive relationship also seen between teacher engagement and teacher satisfaction. In addition, the relationship between teachers’ perceptions of the school climate and their job satisfaction is considerably mediated by their level of engagement with the classroom.